Friends’ Alcohol-Related Social Networking Site Activity Predicts Escalations in Adolescent Drinking: Mediation by Peer Norms - Nesi, Jacqueline (J Adolesc Health, 2017)
PURPOSE: Adolescents’ increased use of social networking sites (SNS) coincides with a developmental period of heightened risk for alcohol use initiation. However, little is known regarding associations between adolescents’ SNS use and drinking initiation, nor the mechanisms of this association. This study examined longitudinal associations among adolescents’ exposure to friends’ alcohol-related SNS postings, alcohol-favorable peer injunctive norms, and initiation of drinking behaviors. METHODS: Participants were 658 high-school students who reported on posting of alcohol-related SNS content by self and friends, alcohol-related injunctive norms, and other developmental risk factors for alcohol use at two time points, one year apart. Participants also reported on initiation of three drinking behaviors: consuming a full drink, becoming drunk, and heavy episodic drinking (three or more drinks per occasion). Probit regression analyses were used to predict initiation of drinking behaviors from exposure to alcohol-related SNS content. Path analyses examined mediation of this association by peer injunctive norms. RESULTS: Exposure to friends’ alcohol-related SNS content predicted adolescents’ initiation of drinking and heavy episodic drinking one year later, controlling for demographic and known developmental risk factors for alcohol use (i.e., parental monitoring, peer orientation). In addition, alcohol-favorable peer injunctive norms statistically mediated the relationship between alcohol-related SNS exposure and each drinking milestone. CONCLUSIONS: Results suggest that social media plays a unique role in contributing to peer influence processes surrounding alcohol use, and highlight the need for future investigative and prevention efforts to account for adolescents’ changing social environments.